Efficient Synthesis of Eight-Membered Cyclic Diaryl Sulfides via an Aryne Reaction with 2-Methylenebenzothiophene-3-Ones - Juhua Feng; Wenjie Zou; Haokun Zhang; Qilin Huang; Ailin Huang; Kuan Liu; Guizhou Yue (Reactions)
In this study, we develop a concise and efficient synthetic strategy for the construction of eight-membered cyclic diaryl sulfides by undertaking [3+2] cycloaddition, 1,2-hydrogen shift, and C(sp2)-S bond cleavage steps on 2-methylenebenzothiophene-3-ones with aryne, using TBAT as the fluorine source. This transformation proceeds well under mild conditions and affords the target products in high to excellent yields (up to 93% yields). The process provides a practical route to achieving sulfur-containing medium-sized heterocycles.